SISTEM INFORMASI PEMBAYARAN BERBASIS RFID PADA PONDOK TAHFIDH YANB’UL QUR’AN 3 BATAM - Lim, Tommy; Silalahi, Mesri (LPPM Universitas Putera Batam, 2023)
The rapid development of information and technology in the digital era has resulted in new technologies appearing that seem endless, especially in the field of education. One of them is in Islamic boarding schools, where the use of this technology includes computers as a means in the process of learning and communicating Arabic writing, Islamic boarding school academic information systems, and cooperative payment information systems. Tahfidh Yanbu'ul Qur'an 3 Batam Islamic boarding school is a branch of Tahfidh Yanbu'ul Qur'an Kudus under the auspices of the Arwaniyyah Foundation. The problem being faced by students and cooperative officers is during snack breaks at the cottage cooperative because the payment process is on a First Come First Serve basis, so it is very time consuming. From these problems, it is necessary to build a payment information system that can simplify and speed up the students to make the payment process in the cooperative. The purpose of this research is to design and build an RFID-based payment information system that is expected to speed up the payment process in cooperatives. The method used by the author is SDLC with the development of an agile Scrum model. With the results of the research that the system that has been built and designed has helped the productivity of the cottage in terms of effectiveness and efficiency.